Analisis Kesalahan Penggunaan Jouken Hyougen pada Pembelajar Bahasa Jepang - Fridasari, Kusnaryati; Sutedi, Dedi; Herniwati, Herniwati (KIRYOKU, 2025)
This study aims to analyze errors in the use of jouken hyougen among learners of the Japanese language. It focuses on identifying the common types of errors and describing the factors that cause these errors. The research employs a mixed-method approach, combining quantitative and qualitative methods. The participants consist of 21 students from Widyatama University, who have studied Japanese for at least two years. Data were collected through written tests, multiple choice questions, true-false questions, and questionnaires. The result of the data analysis reveal that the most frequent errors occured in the use of the tara form, followed by errors in the to and ba forms. Many learners experience difficulties in understanding the appropriate context for each sentence structure, requiring more time to study jouken hyougen, experiencing confusion in distinguishing the different forms, and make mistakes in applying the gramatical rules. The percentage of errors recorded was 52.37% for the to form, 47.61% for the ba form, 76.19% for the tara form, and 33.32% for the nara form. The factors contributing to these errors include learners lack of understanding of the proper function and use of each form in sentences, the influence of interference of their mother tongue, insufficient practice in writing and speaking with jouken hyougen in real life situations, and social factors.